Odpowiedzi

2010-03-21T15:54:41+01:00
{a+b=155
{0,5a= (1/3) b

{a=(155-b)
{0,5a= (1/3) b

0,5 (155-b) = (1/3) b
77,5 -0,5b = (1/3) b
77,5= (1/3)b +0,5b
77,5= (1/3)b +(1/2)b
77,5= (2/6)b +(3/6)b
77,5= (5/6)b
b=93

a=155-93
a=62

odp.
{a=6
{b=93

(1/3) - ułamek jedna trzecia
(1/2) - ułamek jedna druga
2 3 2
Najlepsza Odpowiedź!
2010-03-21T15:56:17+01:00
{a+b=155
{0,5a= (1/3) b

{a=(155-b)
{0,5a= (1/3) b

0,5 (155-b) = (1/3) b
77,5 -0,5b = (1/3) b
77,5= (1/3)b +0,5b
77,5= (1/3)b +(1/2)b
77,5= (2/6)b +(3/6)b
77,5= (5/6)b
b=93

a=155-93
a=62

odp.
{a=6
{b=93

(1/3) - ułamek jedna trzecia
(1/2) - ułamek jedna druga


pozdro
1 1 1
2010-03-21T15:57:13+01:00
* - razy

x + y = 155
0,5x = ⅓y

⅓y * 2 + y = 155
1⅔y = 155 ||*⅗
y = 93

x = 155 - 93
x = 62

Te liczby to 93 i 62.
1 5 1